Kronotop Kontra Politik dan Visualitas Korban dalam Film Dokumenter: Kajian Antropologi Media - Aryo Danusiri (Antropologi Indonesia, 2018)
This article is my retrospective account on the making of one of my testimonial documentaries, “Kameng Gampoeng Nyang Keunong Geulawa” (The Village Goat that Takes the Beating, 1999) which was commissioned by a human rights-defender NGO based in Jakarta. The aim was to offer critical views on the Aceh conflict to the Indonesian public. By using chronotopes (Bakhtin, 1981) as the analytical tool, I delineate the way the Indonesian state and its military constituted a dominant view of Aceh as the Other by applying a semiotic model of authoritarian nationalism that circulated in the public sphere. As the counter-politics, I developed particular testimony chronotopes as a strategy to capture victims’ points of view as embodied experience. In my reflection, I argue that instead of producing a complex visuality of the Aceh actors as human beings, my portrayal of the victims had taken on a sustained oppressor-victim binary opposition view which framed victims as the articulation of singular experience. This study contributes to the emerging interest in media anthropology and the study of non-mainstream film genres and independent cinema works.